Mitigating COVID-19 in Indonesia: The roles of local governments - Ghuzini, Diny (Taylor and Francis, 2022)
The COVID-19 pandemic has slowed regional economic growth of all 34 provinces in Indonesia. Indeed, the pandemic poses great challenges to all sectors and governments at all levels. Provinces that contracted economically by more than 5% in the last the three quarters of 2020 are Riau islands, Special Capital City Region (Daerah Khusus Ibukota or DKI) Jakarta, West Java, Central Java, Yogyakarta, East Java, Banten, Bali, East Kalimantan, West Sulawesi, and West Papua. In the second quarter of 2020, in addition to Riau Islands, Bali, and East Kalimantan, all the provinces in Java were severely affected by the pandemic. This large economic contraction in Java was mainly due to the implementation of large-scale social restrictions and lockdowns in the first half of 2020. As restrictions were eased and social assistance distributed in some provinces, growth rates started to increase albeit at different speeds (Figure 6.1). Bali recorded the lowest growth at –11.06%, showed further drops in subsequent periods. The COVID-19 pandemic indeed devastated Bali’s main industry – tourism. Foreign tourist visits dropped by 99.98% in November 2020 from the previous year, while the GDP shares of accommodation and service industries fell from around 20% in 2019 to 15% in 2020. Unlike other industries that can be effectively stimulated by national and local policies, the effects of a pandemic on a tourism industry that relies heavily on foreign tourists are striking; any rebound effect from the possibility of reinvigorated tourism could be easily reversed by predictions of future waves infection (Bhaskara and Filimonau, 2021). When other provinces’ growth rates were at their lowest, Papua’s growth rate was one of the highest at 4.06% along with Central Sulawesi at 4.49%. Indeed, in 2019 and 2020, Central Sulawesi did better than other provinces with only a slight decrease in growth during the second and third quarters of 2020. By the end of 2020, North Maluku and Papua were amongst the provinces with the fastest recoveries with growth rates of 9.48% and 6.92%. Central Sulawesi also maintained its growth at 4.45% when other provinces’ growths were still negative.